Plasticity of human tendon`s mechanical properties: effects on sport performance - Arampatzis, A. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
In the literature it is often mentioned, that the tendon is very relevant for the work producing capability of the muscle fibers and for the motion and the performance of the human body. In a series of experiments we examined the mechanical properties of the lower extremities muscle-tendon units (MTU) from athletes displaying different running economy and sprint performance. The most economical runners showed a higher contractile strength and a higher tendon stiffness in the triceps surae MTU and a higher compliance of the quadriceps tendon and aponeurosis at low level tendon forces (Arampatzis et al., 2006). The faster sprinters exhibited a higher elongation of the vastus lateralis (VL) tendon and aponeurosis at a given tendon force and a higher maximal elongation of the VL tendon and aponeurosisduring the MVC (Stafilidis and Arampatzis, 2007). Furthermore, the maximal elongation of the VL tendon and aponeurosis showed a significant correlation with the 100 m sprint times (r = -0.567, P = 0.003). It has been supposed that, the more compliant quadriceps tendon and aponeurosis will increase the energy storage and return as well as the force potential of the muscle due to the force-velocity relationship. These studies provide evidence that the mechanical properties of the tendons at the lower extremity at least partially explain the performance of the human musculoskeletal system during running activities. However, until now no study exist in reference to the potential for improving running performance by manipulating the tendon mechanical properties. Mechanical load induced as cyclic strain on connective soft tissues such as tendons is an important regulator of fibroblast metabolic activity as well as for the maintenance of tendon matrix (Chiquet et al., 2003). An increased loading typically stimulates cells for remodelling and, therefore, for increasing the mechanical properties of the tissue (Arnoczky et al., 2002). Whereas, a decreased loading leads to tissue destruction and weak mechanical properties of the tissue (Arnoczky et al., 2004). This paper aimed (a) to present the effects of a controlled modulation of strain magnitude and strain frequency applied to the Achilles tendon on the plasticity of tendon mechanical and morphological properties and (b) to investigate whether an exercise induced increase in tendon-aponeurosis stiffness and contractile strength at the triceps surae muscle-tendon unit affect running economy.